Pemanfaatan Maggot (Balck Soldier Fly) dalam Pengolahan Sampah Organik - Aline Meldiani Windianingsih; Kahar Kahar (Lontara Journal of Health Science and Technology, 2023)
The waste problem is an ongoing and unresolved issue due to the continuous daily activities of humans, which inevitably produce waste. Dealing with a large amount of waste requires proper management, especially for organic waste. The purpose of this study is to describe the utilization of Black Soldier Fly (BSF) larvae in organic waste processing. The research method employed is descriptive-observational, with the total population as the sample. Data collection methods include interviews and observations, and the data were analyzed using frequency distribution. The research findings indicate that the generation of organic waste at the processing site amounts to 1,407.12 kg/day, while the waste generated from a single village is 1,125 kg/person/day, which is categorized as substantial. Based on observations of organic waste processing using BSF larvae at the Integrated Waste Management Site (TPST), it was found that up to 225 kg of organic waste can be processed in one month, thereby reducing the overall amount of organic waste generated. The facilities and infrastructure for organic waste processing using BSF larvae meet the requirements for various stages, including the fly phase, egg phase, hatching phase, larval enlargement phase, prepupa phase, and pupa phase. In conclusion, the utilization of BSF larvae in organic waste processing can effectively reduce the amount of organic waste disposed of at TPST.